Pengaruh Supervisi Akademik Pengawas Sekolah terhadap Peningkatan Kompetensi Profesional dan Kinerja Guru: The Influence of School Supervisors' Academic Supervision on Improving Teachers' Professional Competence and Performance - Sofia Amtaran; Maximus Gorky Sembiring; Riandi Marisa (ITScience (Information Technology and Science), 2026)
The low level of student literacy in Indonesia, particularly in East Nusa Tenggara Province, poses a challenge in improving the quality of education. This condition demands strengthening teacher quality through academic supervision by school supervisors. This study aims to examine the effect of academic supervision on teacher professional competence and performance, both partially and simultaneously. The study used a quantitative approach with a survey method of 328 respondents selected through the Simple Random Sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was carried out using descriptive analysis, simple linear regression, and Multivariate Analysis of Variance (MANOVA) using IBM SPSS version 27. The results of the study indicate that academic supervision has a positive and significant effect on teacher professional competence, with a significance value of 0.000 < 0.05 and a contribution of 58.4%. Academic supervision also has a positive and significant effect on teacher performance, with a significance value of 0.000 < 0.05 and a contribution of 60%. In addition, the results of the Pillai's Trace test indicate that academic supervision simultaneously has a significant effect on teacher professional competence and performance, with a contribution of 40.7%. Thus, academic supervision by school supervisors has a strategic role in improving teacher professionalism and performance as an effort to support improving the quality of education.